Rich Ornaments and Delightful Engines: The Poetics of Failed Festivity and Figural Automation in William Shakespeare’s Titus Andronicus - Agnieszka Żukowska (Anglica. An International Journal of English Studies)
The present study focuses on the poetics of failed festivity in William Shakespeare’s Titus Andronicus, tracing analogies between early modern festival culture, in particular the Joyous Entry of the Renaissance prince into the city, and the machinery of the play, which is set in motion by Titus. The principal element of this machinery is the figure of Lavinia, who can be seen as the inverted version of such wonders of occa- sional architecture and civic pageantry as the automaton, the breathing sculpture and the automatic waterwork. One of the major problems explored is the confrontation of reality and fiction, or human flesh and art, in the manifestly echoic universe of the play, where the objectified automaton-like figure responds to the actions of its animators with its own stirring.